Expression quantitative trait loci associated with performance traits, blood biochemical parameters, and cytokine profile in pigs - Freitas, Felipe André Oliveira; Brito, Luiz F.; Silva-Vignato, Bárbara; Nery Ciconello, Fernanda; Almeida, Vivian Vezzoni de; Cesar, Aline Silva Mello (Frontiers in Genetics, 2025)
Identifying expression Quantitative Trait Loci (eQTL) and functional candidate variants associated with blood biochemical parameters can contribute to the understanding of genetic mechanisms underlying phenotypic variation in complex traits in pigs. We identified eQTLs through gene expression levels in muscle and liver tissues of Large White pigs. The identified eQTL were then tested for association with biochemical parameters, cytokine profiles, and performance traits of pigs. A total of 41,759 SNPs and 15,093 and 15,516 expression gene levels from muscle and liver tissues, respectively, enabled the identification of 1,199 eQTL. The eQTL identified related the SNP rs345667860 as significantly associated with interleukin-6 and interleukin-18 in liver tissue, while the rs695637860 SNP was associated with aspartate aminotransferase and interleukin-6, and rs337362164 was associated with high-density lipoprotein of the blood serum. In conclusion, the identification of three eQTL significantly associated with aspartate aminotransferase and cytokine levels in both serum and liver tissues suggests a potential role for these variants in modulating immune function and overall health in production pigs. Further research is needed to validate these findings and explore their potential for improving pig health and productivity.